The Medicinal Importance of Hydrocotyle asiatica Linn. in Kaduna North Local Government Area of Kaduna State, Nigeria - A. I. Sodimu; J. Appah; M. B. Usman; R. A. Suleiman; G. L. Lapkat (Recent Research Advances in Biology Vol. 8, 2021)
Hydrocotyl asiatica (L.) is commonly used as a medicinal herb in Ayurvedic medicine, traditional African medicine, and traditional Chinese medicine. However, little is known about is medicinal use in Nigeria. Thus, a multistage sampling technique was adopted in selecting 10 marketers and 40 herbal practitioners. Water extract of Hydrocotyle asiatica excreted anti-inflammatory and anti-filarial effect and used as memory enhancer and facilitate excellent learning ability. Questionnaires were purposively administered to key informants in the Kaduna North Local Government Area of Kaduna State, Nigeria. However, only 45 were retrieved in the end. The questionnaire focused on demographic information of respondents, ailment treated, preparation and administration protocols. Results revealed various diseases are treated with H. asiatica, which include: headache, cough scurvy and mouth sore, fibroid, menstrual pain, waist pain, back ache, weak libido, sexually transmitted infections, hypertension, amongst others. This herbaceous species can be used alone or mix with other herbs such as Pipper guineensis, Ocimum grandiflorum, Allium cepa, amongst other. Standardization of measurement in the use of H. asiatica is through the use of table and tea spoons. However, it is recommended that adequate storage facilities should be provided to check excessive dryness of the kola and pest infestation during storage. Also, the sustainability of biodiversity and biological resources of the species and other important medicinal plants should be ensured so that individual plants do not go into extinction.